Biorefinery roadmap based on catalytic production and upgrading 5-hydroxymethylfurfural. Issue 1 (23rd December 2020) - Hou, Qidong; Qi, Xinhua; Zhen, Meinan; Qian, Hengli; Nie, Yifan; Bai, Chuanyunlong; Zhang, Shiqiu; Bai, Xinyu; Ju, Meiting
Abstract : This review presents a comprehensive roadmap for the production of HMF from biomass and the upgradation of HMF toward fuels, chemicals and materials. Abstract : Biorefineries, which utilize lignocellulosic biomass as renewable energy source and sustainable carbon feedstock, are a promising solution to alleviate the excessive dependence on the depleting fossil resources and address climate change and other environmental problems. Owing to the recalcitrance and over-functionalized nature of biomass, the conversion of biomass into desirable products requires a series of complex deconstruction, catalytic conversion, separation and purification processes. In the biorefinery roadmap, 5-hydroxymethylfurfural (HMF) stands out as a bridge connecting biomass raw materials to alternative fuels, chemicals and materials, which can displace petroleum-derived products. This review describes the recent advances in the design and development of catalytic systems for the conversion of biomass and their constituent carbohydrates to HMF via hydrolysis, isomerization and dehydration reactions, and the upgrading of HMF towards polymer monomers, fine chemicals, fuel precursors, fuel additives, liquid fuels, and other platform chemicals via hydrogenation, oxidation, esterification, etherification, amination and aldol condensation reactions, with emphasis on how the catalysts, solvents and reaction conditions determine the reaction pathway and product selectivity. We also attempt to provide a conceptual framework on how to evaluate the actual reaction efficiency, reusability, and economic and technical feasibility of different catalytic systems and highlight the key research challenges to be addressed.